Electron‐Scale Front of Magnetic Pile‐Up Region in Reconnection Exhaust. Issue 2 (2nd February 2023) - Chen, Z. Z.; Liu, C. M.; Yu, J.; Wang, T. Y.; Wang, J.; Cui, J.; Cao, J. B.
Abstract: The magnetic pile‐up region and its front, which plays a crucial role in electron energization during magnetic reconnection, has been widely studied at fluid and ion scales. However, there have been few studies on electron‐scale front of magnetic pile‐up regions so far. Here, we present detailed observations of electron‐scale front in a tailward reconnection exhaust. With a thickness of ∼5.5 de (electron inertial length), the front propagated along its normal direction, mainly along the reconnection outflow direction. At this front, the strong energy conversion observed was mainly driven by the perpendicular electron current. The front can lead to adiabatic electron heating and acceleration. The front hosts an intense and highly structured electric field, reaching up to ∼120 mV/m and predominantly attributed to the electron convection term. Electrostatic waves with frequencies higher than the electron gyrofrequency and parallel normal angles (WRT background magnetic field) were detected adjacent to the front. Our study can provide insight into the roles of fronts and electron‐scale physics in magnetic reconnection. Plain Language Summary: Magnetic pile‐up regions and the associated front can be formed close to the reconnection site by the interaction of reconnection outflow with preexisting plasmas. They play significant roles in flux transport, energy conversion, and particle energization, and have been widely studied at magnetohydrodynamics and ion scales. Recently, electron‐scale measurements indicate that electron‐scale processes can modify dynamics in these regions. However, there is so far no observation of electron‐scale front of magnetic pile‐up regions. Thus, it is unclear what properties of electron‐scale front are and whether electron‐scale front can play roles in magnetic reconnection. Here, we present detailed observations of such electron‐scale front in a tailward reconnection exhaust. Our results suggest the importance of such electron‐scale structure in magnetic reconnection. Key Points: An electron‐scale front with a thickness of ∼5.5 de was observed in a tailward reconnection exhaust Strong energy conversion, electron heating and acceleration were observed simultaneously with the front The electron convection term makes important contributions to the strong electric field measured at the front